The Impact of Immigration on Wages and Employment in the UK Using Longitudinal Administrative Data - Sara Lemos; Jonathan Portes (Institute of Labor Economics (IZA), 2025)
We study the labour market impact of immigration to the United Kingdom, focusing on the large inflows following the 2004 EU enlargement. Using the Lifetime Labour Market Database (LLMDB)—a longitudinal 1% sample of National Insurance records—we provide the first analysis of immigration's effects on employment and wages based on high-quality administrative microdata. Exploiting individual, area and time fixed effects, as well as area-time, individual-time and individual-area fixed effects, we reduce endogeneity concerns that have limited previous work. We find limited aggregate impacts, but distributional consequences: existing immigrants—particularly those who were young or low paid—experienced modest negative employment effects, while natives faced little evidence of displacement. For wages, impacts were mixed: existing immigrants overall gained, but low-paid immigrants lost. The results suggest labour market adjustment operated through both substitution and complementarities across groups. More broadly, we provide a methodological framework for analysing the much larger and more diverse post-2021 immigration flows.
Keywords: J22; C23; 330; immigration; employment; wages; Central and Eastern Europe; UK